1346 Hardware Complications in Cephalomedullary Nailing for Intertrochanteric Hip Fractures: A Retrospective Cohort Study. (12th October 2021) - Legg, P; To, C; Selmon, G
Abstract: Introduction: Intertrochanteric hip fractures are common injuries in elderly patients and can result in significant morbidity. The use of cephalomedullary femoral nailing (CMN) has gained popularity, particularly for unstable fracture patterns. We investigated hardware complications and mortality of patients undergoing long and short CMN for intertrochanteric hip fractures. Method: We conducted a retrospective cohort study of consecutive cases in a single UK-based trauma unit between 01 July 2016 – 31 Dec 2019. Primary outcome measures were implant failure and revision surgery. The secondary outcome measure was mortality. Results: 335 patients were included, mean age 82.9 years. 176 long (LN) and 167 short (SN) CMNs were performed. 25/335 (7.5%) hardware complications occurred resulting in 19 (5.7%) revision surgeries. Overall implant survivorship was 94.3%. There was no statistically significant difference in implant survivorship between LN and SN (p = 0.93), or between proximal screw configuration (p = 0.20). Cox regression analysis did not identify any independent predisposing factors leading to hardware complications. 30-day, 90-day and 1-year mortality rates were 7.9%, 15.2% and 26.5% respectively. There was no significant difference in mortality between LN and SN (p = 0.53). Regression analysis identified age and male gender as statistically significant independent factors of increased mortality. Conclusions: For intertrochanteric fractures, there is no difference in hardware complications or mortality between long and short cephalomedullary nails. We highlight the risk of implant fracture at the lag screw-nail interface; accounting for one-quarter of failures. The revision rate of 5.7% due to hardware failure should be a consideration for surgeons undertaking CMN for intertrochanteric fractures.